Continuous enzyme-coupled assay of phosphate- or pyrophosphate-releasing enzymes. (August 2012) - Suárez, Antonio S. Guillén; Stefan, Alessandra; Lemma, Silvia; Conte, Emanuele; Hochkoeppler, Alejandro
A coupled enzyme assay able to monitor the kinetics of reactions catalyzed by phosphate- or pyrophosphate-releasing enzymes is presented here. The assay is based on the concerted action of inorganic pyrophosphatase (PPase), purine nucleoside phosphorylase (PNPase), and xanthine oxidase (XOD). In the presence of phosphate, PNPase catalyzes the phosphorolysis of inosine, generating hypoxanthine, which is oxidized to uric acid by XOD. The uric acid accordingly formed can be spectrophotometrically monitored at 293 nm, taking advantage of a molar extinction coefficient which is independent of pH between 6 and 9. The coupled assay was tested using DNA polymerases as a model system. The activity of Klenow enzyme was quantitatively determined, and it was found in agreement with the corresponding activity determined by traditional methods. Moreover, the continuous coupled assay was used to determine K m and V max of Klenow enzyme, yielding values in good agreement with previous observations. Finally, the coupled assay was also used to determine the activity of partially purified DNA polymerases, revealing its potential use to monitor purification of phosphate- or pyrophosphate-releasing enzymes.